The dynamics of the age structure, dependency, and consumption - Heinrich Hock; David N. Weil (Brown University, Department of Economics, 2006)
We examine the dynamic interaction of the population age structure, economic dependency, and fertility, paying particular attention to the role of intergenerational transfers. In the short run, a reduction in fertility produces a “demographic dividend” that allows for higher consumption. In the long run, however, higher old-age dependency can more than offset this effect. To analyze these dynamics we develop a highly tractable continuous-time overlapping generations model in which population is divided into three groups (young, working age, and old) and transitions between groups take place in a probabilistic fashion. We show that most highly developed countries have fertility below the rate that maximizes steady state consumption. Further, the dependency-minimizing response to increased longevity is to raise fertility. In the face of the high taxes required to support transfers to a growing aged population, we demonstrate that the actual response of fertility will likely be exactly the opposite, leading to increased population aging. – Aging ; fertility ; intergenerational transfers ; consumption
Keywords: E10; E21; H55; J11; J13; 330; Privater Transfer; Overlapping Generations; Fruchtbarkeit; Gesamtwirtschaftlicher Konsum; Theorie; Altersstruktur der Bevölkerung